2012
DOI: 10.1063/1.4759161
|View full text |Cite
|
Sign up to set email alerts
|

Formation of jet-like spikes from the ablative Rayleigh-Taylor instability

L. F. Wang,
W. H. Ye,
X. T. He
et al.

Abstract: The mechanism of jet-like spike formation from the ablative Rayleigh-Taylor instability (ARTI) in the presence of preheating is reported. It is found that the preheating plays an essential role in the formation of the jet-like spikes. In the early stage, the preheating significantly increases the plasma density gradient, which can reduce the linear growth of ARTI and suppress its harmonics. In the middle stage, the preheating can markedly increase the vorticity convection and effectively reduce the vorticity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…As the ablated plasma fills the volume within the bubbles, the vorticity accumulates, providing a centrifugal force that acts on the bubble's wall. Similar vorticity accumulation and bubble acceleration phenomena were also reported by Wang et al 13 In 2D geometry, 12 the bubble acceleration vanishes asymptotically and the bubble's velocity saturates at a value above its classical value U cl2D b . Another numerical study by Igumenshchev et al 14 showed that a small defect on the target surface with a 10 lm radius and 1 lm height drives an RTI bubble that quickly penetrates through the shell.…”
Section: Introductionsupporting
confidence: 85%
“…As the ablated plasma fills the volume within the bubbles, the vorticity accumulates, providing a centrifugal force that acts on the bubble's wall. Similar vorticity accumulation and bubble acceleration phenomena were also reported by Wang et al 13 In 2D geometry, 12 the bubble acceleration vanishes asymptotically and the bubble's velocity saturates at a value above its classical value U cl2D b . Another numerical study by Igumenshchev et al 14 showed that a small defect on the target surface with a 10 lm radius and 1 lm height drives an RTI bubble that quickly penetrates through the shell.…”
Section: Introductionsupporting
confidence: 85%
“…[11] Especially, in the implosion process of ICF, the ablation effect makes the material distribution in the capsule more complicated. [12][13][14][15][16] The classic RTI models which only include a single material interface are not good enough for depicting the perturbation growth of the RTI with multiple interfaces. However, to understand the mechanism of the RTI with multiple interfaces, some efforts have been done by researchers.…”
Section: Introductionmentioning
confidence: 99%
“…The Rayleigh-Taylor instability has been investigated analytically, [6][7][8][9][10][11][12][13][14][15][16][17][18] numerically, [19][20][21] and experimentally [22,23] by many researchers. The classical RTI is first given by Rayleigh, [1] where two semi-infinite fluids are separated by a perturbed interface.…”
Section: Introductionmentioning
confidence: 99%